The role of cooperatives in democratization and development A case of Uson Small Coconut Farmers Multi-Purpose Cooperative. - Coton, Vennie G. (Vennie G. Coton, 2009)
The study wants to know how cooperative contribute to the economic development and how it facilitate the democratization process. The focus of this study is the Uson Small Coconut Farmers Multi-Purpose Coopeative or USCOFAMCO.